2016
DOI: 10.1002/cctc.201601162
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Hydrodeoxygenation of Stearic Acid to n‐Heptadecane and n‐Octadecane by Adjusting the Chemical Properties of Ni/SiO2–ZrO2 Catalyst

Abstract: A series of SiO2–ZrO2 mixed oxides with varying SiO2 concentrations were hydrothermally synthesized and used as support for Ni in the hydrodeoxygenation of stearic acid. ZrO2 provides a relatively low surface area and only Lewis acid sites, and Ni supported on ZrO2 produces n‐heptadecane from stearic acid through hydrogenation and decarbonylation. The SiO2–ZrO2 mixed oxides have a higher specific surface area than ZrO2 as well as an unprecedented spherical and nanolayered morphology. Brønsted acid sites were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…The absence of chlorine eliminated its poisoning effect, concerning the selective deoxygenation sites. On the other hand, the change of the zirconium salt brought about the partial reduction of ZrO 2 to sub-oxide (ZrO x ), which participates on the reaction mechanism through defect oxygen sites [24][25][26][27], and an increase of the Ni surface exposed. According to Foraita et al [26], SDO can be catalyzed solely by Ni, but the synergistic interaction between Ni and the ZrO 2 influences the reaction rates.…”
Section: Second Series Of Catalysts: Effect Of the Preparation Paramementioning
confidence: 99%
See 2 more Smart Citations
“…The absence of chlorine eliminated its poisoning effect, concerning the selective deoxygenation sites. On the other hand, the change of the zirconium salt brought about the partial reduction of ZrO 2 to sub-oxide (ZrO x ), which participates on the reaction mechanism through defect oxygen sites [24][25][26][27], and an increase of the Ni surface exposed. According to Foraita et al [26], SDO can be catalyzed solely by Ni, but the synergistic interaction between Ni and the ZrO 2 influences the reaction rates.…”
Section: Second Series Of Catalysts: Effect Of the Preparation Paramementioning
confidence: 99%
“…These results encourage us to extend our study to co-precipitated nickel-zirconia catalysts. Very few studies have devoted to nickel catalysts supported on zirconia [24][25][26][27][28][29]. In the most of cases the catalysts, with nickel content 3-15 wt %, were prepared by incipient wetness impregnation [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of time on conversion and yields could provide useful information for optimizing and scaling up a process. The effect of time, particularly in batch and semi-batch reactors, is typically evaluated to obtain useful information about deoxygenation pathways as well as product evolution (Foraita et al, 2017). Reaction pathways are interesting because they enable scientists to rationally design new catalytic systems, while product evolution over time may indicate an opportunity to maximize the yield of some products (Stellwagen and Bitter, 2015).…”
Section: Contact Timementioning
confidence: 99%
“…Some researchers have found that the acidity of a support impacts the deoxygenation of fatty acids and esters on metal catalysts . In the deoxygenation reaction of methyl palmitate, Ni/SAPO‐11, containing weak and medium acid sites, exhibited a superior deoxygenation performance to Ni/SiO 2 .…”
Section: Introductionmentioning
confidence: 99%